HISTORICAL DEVELOPMENT OF TAX DURING THE EARLY ISLAMIC PERIOD: JIZYAH AND KHARAJ: A Historical Analysis - Muchsin, Misri Abdul; Manan, Abdul (Journal of Al-Tamaddun, 2019)
Tax has been existed since the early era of Islam; in Medina, the Prophet Muhammad had implemented the taxation system called Jizyah. Kharaj (as a part of Ghanimah) was introduced during the era of caliph Umar bin al-Khattab. This article discussed the taxation system in the early period of Islam. Historical approach was applied in combination of normative Islam in explaining the issue. The result indicated that Jizyah and Kharaj were included to tax in the early era of Islam. Jizyah referred to tax which must be paid by Ahli Dhimmah (non-believers who are citizen of Islamic state), which had been applied based of al-Quran and Sunnah since the era of Prophet’s governance in Medina. Jizyah was also applied by the caliphs after the era of Prophet Muhammad. However, some orientalists considered it as a disgrace for non-believers. On the other hand, Kharaj referred to land tax as a part of Ghanimah. Kharaj was originated of Umar bin al-Khattab’s idea and in the beginning, several people disagreed that it became a source of Baitul Mal. Both of Jizyah and Kharaj were the largest sources of income for Muslim in the early period of Islam. Umar bin al-Khattab who applied Kharaj had meritorious role toward the development of Baitul Mal. Then, his governance became reference upon the implementation of Jizyah and Kharaj as Islamic taxation method.